(untitled) (Journal of Science and Technology Research, 2024)
The research was carried out in a few selected regions of Bangladesh from July 2022 to June 2023 to explore the current status, reproductive behavior, and health management of captive common peafowl (Pavo cristatus). Ten peafowl farmers were interviewed using pre-structured questionnaire to collect primary data. The data were processed, and then illustrated in tabular form employing descriptive statistical analyses. The majority of the farmers were aged between 31 to 50 years, with 50% engaged in business. They became interested in peafowl farming through social media, other farmers, and friends. Notably, most of the farmers reared India Blue variety of common peafowl. They had neither prior experience nor participated in any training programs on peafowl farming. The adult male peafowl (peacock) significantly (P<0.0001) outweighed female peafowl (peahen). The age of first laying for peahens was around 2 years. Majority of the farmers reared 21 to 60 birds with an average egg production of 22.90±1.43 eggs/bird/year. The mean egg weight and clutch size were 95.70±4.54 g and 9.30±0.47 eggs, respectively. The average incubation time was 28.90±0.43 days. Fertility and hatching rates were 87.30±1.40 and 74.30±1.07%, respectively. Majority of the farmers (80%) used poultry feed for feeding peafowls and routinely used drugs and additives in the feed and water. Forty percent of the farmers sought veterinary advice and 60% implemented general biosecurity procedures. The prevalence of Newcastle disease (20.70%) was significantly (P<0.0001) higher compared to other diseases. Despite numerous challenges, peafowl farming in Bangladesh was found to be highly profitable in comparison to the costs. However, effective training programs, research initiatives, and strategic marketing efforts are crucial for the development of peafowl farming as a new income generating venture in the country. Therefore, peafowl farming could flourish with targeted interventions and support from both the government and private enterprises in Bangladesh. J. of Sci. and Tech. Res. 6(1): 21-32, 2024